2020
DOI: 10.17680/erciyesiletisim.713467
|View full text |Cite
|
Sign up to set email alerts
|

Nefret Söyleminin İnşasında Sosyal Medyanın Rolü: Ekşi Sözlük Örneği

Abstract: It can be said that continuous hate speech is produced intensely in daily life and is reproduced by sharing them on different media, especially on social media. In this study, the hate speech that is produced and circulated on Ekşi Sözlük (one of the most used social media platforms) is investigated. In this context, the title of "Syrian Refugees" on Ekşi Sözlük is determined as the sample of the study. Under this title, it is aimed to reveal how users express their prejudices, discontent, and intolerance, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Various psychological phenomena were investigated in the literature using the Ekşi Sözlük -one of the online collaborative dictionaries-as a source. For example, hate speech toward different groups such as Chinese (Tunçer, 2020), Armenians (Akkılıç, 2018), gypsies (Alp, 2016), Syrians (Yaşa, 2017), and Jews (Öztekin, 2015), representations of significant people (Erdem & Bardak, 2010), reactions to current events such as murders of women (Kekeç Gören & Taşçıoğlu, 2018) or acceptance of the women writers to the Ekşi Sözlük (Aslantürk & Turgut, 2015). There is a couple of research on gender on Ekşi Sözlük.…”
Section: The Current Studymentioning
confidence: 99%
“…Various psychological phenomena were investigated in the literature using the Ekşi Sözlük -one of the online collaborative dictionaries-as a source. For example, hate speech toward different groups such as Chinese (Tunçer, 2020), Armenians (Akkılıç, 2018), gypsies (Alp, 2016), Syrians (Yaşa, 2017), and Jews (Öztekin, 2015), representations of significant people (Erdem & Bardak, 2010), reactions to current events such as murders of women (Kekeç Gören & Taşçıoğlu, 2018) or acceptance of the women writers to the Ekşi Sözlük (Aslantürk & Turgut, 2015). There is a couple of research on gender on Ekşi Sözlük.…”
Section: The Current Studymentioning
confidence: 99%
“…The rise of anti-Syrian discourses and even hate speech have been apparent in the social media in Turkiye as well and there are studies analyzing these discourses (Özerim & Tolay, 2021;Küçük & Koçak, 2020;Yaşa & Öksüz, 2020;Bozdağ, 2019;İşçi & Uludağ, 2019;Toprak, 2018;Kardeş, Banko, & Akman, 2017;Özdemir & Öner-Özkan, 2016;Yıldırım & Yurtdaş, 2016). A study (Bozdağ, 2019) analyzing discursive positions about Syrian refugees on Twitter showed how a discussion on Syrians' citizenship gave way to pro-and anti-Syrian discourses simultaneously.…”
Section: Social Media and Anti-immigrant Attitudesmentioning
confidence: 99%
“…Bu araştırmanın kapsamı, söz konusu tartışmanın Ekşi Sözlük üzerinde mevcut "entry" içerikleriyle sınırlıdır. "Ekşi Sözlük'te bir başlık altına sözlük yazarları tarafından yazılan açıklama, tanım ya da yorumlara entry adı verilmektedir" (Yaşa ve Öksüz, 2020(Yaşa ve Öksüz, : 1404. Sözlük üzerinden yapılan arama sonucunda konuyla doğrudan ilgili ve en fazla sayıda entry içeren, lansman filminin yayınlanmasının ardından, 22 Eylül 2021 tarihinde açılmış olan "ebrar karakurt'lu elidor reklamı" başlığı araştırma için veri kaynağı olarak seçilmiştir (Ekşi Sözlük, 2021).…”
Section: Araştırmanın Amacı Kapsamı Ve Yöntemiunclassified
“…Genel olarak kullanıcı görüşleri bağlamında ya da Ekşi Sözlük özelinde gerçekleştirilmiş farklı çalışmalarda (Alp, 2016;Yaşa ve Öksüz, 2020) olduğu gibi, her bir entry özelinde markaya, kampanyaya ya da ünlüye yönelik genel görüşü kodlamak üzere "olumlu, olumsuz, nötr" biçiminde ana kategoriler oluşturulmuştur. Ek olarak, bazı 'entry'lerin nötr olarak kodlanamayacak düzeyde lehte ve aleyhte görüşleri birlikte içermesi durumunda kullanılmak üzere "hem olumlu hem olumsuz" biçiminde dördüncü bir kategori oluşturulmuştur.…”
Section: Araştırmanın Amacı Kapsamı Ve Yöntemiunclassified
See 1 more Smart Citation